Cattle manure and liming for guanandi seedlings production - Artur, Adriana Guirado; Cruz, Mara Cristina Pessôa da; Ferreira, Manoel Evaristo; Barretto, Vitor Corrêa de Mattos; Yagi, Renato (Pesquisa Agropecuaria Brasileira, 2007)
The effects of cattle manure and lime levels in substrate were evaluated to produce guanandi (Calophyllum brasiliense Cambèss.) seedlings in greenhouse conditions. Four levels of each factor were evaluated, in a factorial scheme 4x4. The experimental design was completely randomized with four replicates, each plot with five seedlings. The substrate was obtained by the mixture of eight subsoil parts and two sand parts (v:v). The manure was applied in 0, 2, 4 and 6 parts, in volume, that correspond, in mass, to 0, 101, 175 and 229 kg m-3. Lime doses were calculated to increase the base saturation degree near to 20% (original subsoil sample), 35, 50 and 65%. Seedlings harvest was performed 120 days after transplant, when height, stem diameter, leaf number, leaf area, shoot and root dry matter were evaluated. For substrate constituted by subsoil+sand, the liming and the cattle manure are not necessary to produce guanandi seedlings.